Four receptor‐like cytoplasmic kinases regulate development and immunity in rice. (12th February 2016) - Zhou, Xiaogang; Wang, Jing; Peng, Chunfang; Zhu, Xiaobo; Yin, Junjie; Li, Weitao; He, Min; Wang, Jichun; Chern, Mawsheng; Yuan, Can; Wu, Wenguan; Ma, Weiwei; et al.
Abstract: Receptor‐like cytoplasmic kinases (RLCKs) represent a large family of proteins in plants. However, few RLCKs have been well characterized. Here, we report the functional characterization of four rice RLCKs – OsRLCK57, OsRLCK107, OsRLCK118 and OsRLCK176 from subfamily VII. These OsRLCKs interact with the rice brassinosteroid receptor, OsBRI1 in yeast cell, but not the XA21 immune receptor. Transgenic lines silenced for each of these genes have enlarged leaf angles and are hypersensitive to brassinolide treatment compared to wild type rice. Transgenic plants silenced for OsRLCK57 had significantly fewer tillers and reduced panicle secondary branching, and lines silenced for OsRLCK107 and OsRLCK118 produce fewer seeds. Silencing of these genes decreased Xa21 gene expression and compromised XA21‐mediated immunity to Xanthomonas oryzae pv. oryzae . Our study demonstrates that these OsRLCKs negatively regulate BR signalling, while positively regulating immune responses by contributing to the expression of the immune receptor XA21. Abstract : Very few receptor‐like cytoplasmic kinases (RLCKs) in rice have been well characterized. We found that four rice RLCKs – OsRLCK57, OsRLCK107, OsRLCK118 and OsRLCK176 from subfamily VII interact with the rice brassinosteroid receptor, OsBRI1, and negatively regulate BL‐mediated signalling. Silencing each of the four OsRLCK genes leads to a decrease in Xa21 gene expression and compromises XA21‐mediated immunity to Xoo . Our findings proved that the four OsRLCKs regulate both development and immunity in rice.